Analysis of Physical and Chemical Properties in Comparison Using Goroho Banana Flour (Musa acuminate) and Corn Flour (Zea mays) in the Production of Dry Noodles - ANATJE LIHIANG (Research Parks Publishing LLC, 2022)
Goroho banana flour (Musa acuminate) and corn flour (Zea mays) are non-wheat flours which have quite high starch content, so they have the potential to be used as noodles. The quality of goroho banana flour is influenced by its starch content. The higher the level of substitution of goroho banana flour added, the starch content increases, because goroho banana flour has a higher starch content than wheat flour. The purpose of this study was to determine the physical and chemical properties of the comparison of the use of goroho banana flour and corn flour in the manufacture of dry noodles. The process of making noodles consists of mixing ingredients, steaming, compacting dough, forming sheets and strands, steaming noodles, drying and packaging. The treatment used is flour from goroho bananas and corn flour which is 50 percent: 50 percent, 60 percent goroho banana flour: 40 percent corn flour and 70 percent goroho banana flour: 30 percent corn flour. The results showed that the best noodles were produced by 60 percent goroho banana flour and 40 percent corn flour. With the physical properties of the resulting noodles, namely elongation of 238.76 percent; hardness of 635.88 gf; elasticity of 0.783 gf; and yield of 77.23 percent. The chemical properties of the noodles produced were 9.83 percent water content, 0.91 percent fat, 7.07 percent protein, 1.29 percent ash, 1.73 percent crude fiber, and 73.84 percent starch. With the physical properties of the resulting noodles, namely elongation of 238.76 percent; hardness of 635.88 gf; elasticity of 0.783 gf; and yield of 77.23 percent. The chemical properties of the noodles produced were 9.83 percent water content, 0.91 percent fat, 7.07 percent protein, 1.29 percent ash, 1.73 percent crude fiber, and 73.84 percent starch. With the physical properties of the resulting noodles, namely elongation of 238.76 percent; hardness of 635.88 gf; elasticity of 0.783 gf; and yield of 77.23 percent. The chemical properties of the noodles produced were 9.83 percent water content, 0.91 percent fat, 7.07 percent protein, 1.29 percent ash, 1.73 percent crude fiber, and 73.84 percent starch.